Analyzing the Capital Structure, Economic Value Added, Firm Value and Environmental Performance in Indonesia - Berlianti, Maulidia; Lindrianasari, Lindrianasari; Komalasari, Agrianti (Indonesia Academia Research Society, 2023)
The palm oil industry is one of Indonesia's largest foreign exchange earners and is directly associated with the job creation act had divided opinions regarding the job creation law. Positive reactions were exhibited, particularly by palm oil entrepreneurs, because one of the purposes of the law is the ease of obtaining business permits, which will facilitate investor attraction. This study provides empirical evidence in improving the capital structure, economic value added, firm value, and environmental performance of plantation companies listed on the Indonesian Stock Exchange after implementing Indonesian Act No.39 of 2014 concerning plantations. A total of 10 plantation companies listed on the Indonesian Stock Exchange from 2010-2019 were used as the sample, and the independent t-test was the analytical method employed. Subsequently, the research found an improvement after implementing Indonesian Act No.39 of 2014 concerning plantations. These results are expected to provide useful information and contributions for prospective investors of plantation companies, as well as assist in the formation of laws by the government.